Synthesis of Novel tricyclic pyrazolo(1,4)oxathiinopyrazines and Evaluation of Their Competency Towards the Inhibition of Lactate Dehydrogenase Activity-Inhibition of LDH Activity - Mukherjee, Prasun; Das, Asish R.; Mishra, Raghwendra; Bhowmick, Shovonlal; Saha, Achintya (Drug Research, 2018)
We have evaluated the LDH inhibitory property of novel pyrazolo[4′,3′:5,6][1,4]oxathiino[2,3-b]pyrazine derivatives which have been synthesized from easily available starting materials through a one-pot protocol that offers the use of elemental sulfur as the sulfur source. These newly synthesized compounds may aid to drug development for neoplastic and non-neoplastic diseases characterized by increased glucose metabolism. Additionally, they may act as suitable starting materials which can be further structurally modified for the development of new LDH inhibitors with higher efficacy and specificity.
Keywords: pyrazolo[4′,3′:5,6][1,4]oxathiino[2,3-b]pyrazines; LDH inhibition; Elemental sulfur; One-pot protocol